Advances in Systems Safety Proceedings of the Nineteenth Safety-Critical Systems Symposium, Southampton, UK, 8-10th February 2011 - Dale, Chris; Anderson, Tom (Springer London, 2011)
Advances in Systems Safety contains the papers presented at the nineteenth annual Safety-Critical Systems Symposium, held at Southampton, UK, in February 2011. The Symposium is for engineers, managers and academics in the field of system safety, across all industry sectors, so the papers making up this volume offer a wide-ranging coverage of current safety topics, and a blend of academic research and industrial experience. They include both recent developments in the field and discussion of open issues that will shape future progress. The 17 papers in this volume are presented under the headings of the Symposium?s sessions: Safety Cases; Projects, Services and Systems of Systems; Systems Safety in Healthcare; Testing Safety-Critical Systems; Technological Matters and Safety Standards. The book will be of interest to both academics and practitioners working in the safety-critical systems arena.